Analisis Penjadwalan Proyek Remote Terminal Unit dengan Penerapan Metode CPM dan PERT di PT. XYZ - Tata Sugiarta (Universitas Bunda Mulia, 2021)
ABSTRACT Analysis of the project implementation needs to be done so that deficiency andweaknesses can be identified, as well as problems encountered so that they can beused as reference material for subsequent projects. Project delays are often caused by lack of planned project activities and lack of control over the course of the project so that project implementation activities become less effective and efficient. The Critical Path Method (CPM) and PERT (Program Evaluation and Review Tecnique) are carried out to get an idea of what if the project is controlled by the two tools. Analysis of research results from the Remote Terminal Unit (RTU) project using the CPM method obtained a completion time of 104 days, while completion by the PERT method obtained time of 106.7 days with a probability of 99.99% completion and by processing the Fishbone Diagram there was a cause for the delay factor The biggest is the existence of material delays and the lack of supervision from the company. Keywords : Scheduling, CPM and PERT Methods, Fishbone Diagrams.